Research and public policy in Nigeria - Kumo, Suleimanu; Aliyu, Abubakar; Ahmadu Bello University (Zaria : Dept. of Research and Consultancy, Institute of Administration, A.B.U., 1977)
This book contains the edited proceedings and papers presented at the 1976 conference. The book is divided into four parts. Part 1 deals with issues in Research and Policy Making. Part 2 deals with Research and Data Components of policy Development, while part 3 and 4 has to do with discussion on the important issue of Environmental Management and the consensus arrived at during the conference.
The report of a Conference on Research and Public Policy, Priorities and Strategies held at the Institute of Administration, Ahmadu Bello University, Zaria, 22nd-25th March, 1976
Includes bibliographical references.
hza 11/07/2018
Loans
Keywords: Social sciences; Environmental policy; Nigeria